Nanocomposite Coatings : Novel Approach in Thin Film Industry - Mishra, Dr. Rahul (JOURNAL OF INDUSTRIAL RELATIONSHIP CORPORATE GOVERNANCE AND MANAGEMENT EXPLORER, 2022)
From the above review it can be concluded that nanocomposite coatings represent the state of art in coatings today. The high hardness of the nanocomposite coatings, especially in nc-AlTiN/a-Si3N4 is mainly due to the phase segregation process that forms c-AlTiN rich phase and a-Si3N4 rich domains. The three dimensional skeletal structure of silicon nitride and the nanocrystalline grains of metal nitrides reduce and hinder the movement of dislocation. Several studies have been carried out to study the oxidation behaviour. However there is still a need to study the wear mechanism and behaviour of these coatings under dry machining in hard cut materials such Austenitic stainless steel, titanium alloys etc. Keywords: Nanocomposite coatings, hardness, oxidation resistance, wear resistance